Exploring the Classification and Restructuring of Chemical Industrial Cities in China: The Perspectives of Sectoral and Spatial Differences - Hui Zou; Xuejun Duan; Lei Wang; Tingting Jin (Complexity)
As an economic pillar, major resource consumer, and polluter of cities, the chemical industry determines many cities’ transformation, prosperity, and decay. It is thus a major concern for achieving the UN Sustainable Development Goals. In China, which is at the stage of accelerated industrialization that is varied across regions, the chemical industry has gradually retreated from developed cities, such as Beijing and Shanghai, in the eastern region, and has become the inevitable choice for industrialization of less-developed cities, such as Xi’an, Chengdu, and Chongqing, in the western region. This study took the perspectives of chemical industrial sectors and their spatial differences to understand the changing patterns of the chemical industry and its dominant cities. It identified chemical industrial cities (CICs), examined their spatial-temporal patterns with respect to their industry scale and structure, and accounted for factors influencing the spatial evolution from coastal areas to inland regions. The results show that large CICs were mainly located in coastal port regions with balanced industrial sectors, while small CICs were mainly distributed in inland areas with abundant oil and coal resources and a single dominant industrial sector. The location factors of ports, markets, and technology play important roles in the eastern region, while resource conditions and foreign direct investment promote the chemical industry’s development in the central, western, and northeastern cities. These findings improve the understanding of CICs’ spatial transformation and shed light on the policy-making of chemical industrial development in China and other developing countries.